Corporate Governance And Performance Of Peer Firms: A Cross-Lagged Analysis Of An Emerging Economy - Ali, Rizwan; Liu, Yanping; Niazi, Gul Rukh (Journal of Applied Business Research, 2017)
In this study, we examine the effects of corporate governance practices on financial performance of Pakistani listed firms. On the bases of agency theory, MM theorem, and theory of firm, we suggest that corporate governance effects firm performance directly as well as indirectly via mediation of capital structure and dividend policy. The model was tested using a cross-lagged analysis of 100 non-financial firms with the structural equation modeling (SEM). The study concludes that corporate governance improves financial performance by exploiting capital structure and dividend policy. The findings of this study, highlights the importance of corporate governance practices for peer firms to restructure their debt and dividend policies for the enhancement of their financial performance.
Keywords: Corporate Governance; Capital Structure; Dividend Policy; Firm Performance; Cross-Lag Analysis